TRAINING AND ASSISTANCE IN PIRT REGISTRATION PROCEDURES TO INCREASE MSME EXISTENCE - Zusnita, Wa Ode; Alamanda, Amelia Rizky; Islam Usman Tinumbang, Mushab (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
In today's global era, food safety and health is becoming more complex because food safety is multi-sectoral and multidisciplinary. As we all know, there is no doubt that quality assurance of food safety throughout the food chain is a must without ignoring the fact that more than 200 diseases are spread through daily food. This is the main reason for the government to create a Home Industry Food Production Certification (SPP-IRT) as a guarantee of health quality and food safety from MSMEs (Micro, Small and Medium Enterprises) households. However, the lack of home industry products that have SPP-IRT is a challenge and a problem for the government, society, and MSMEs themselves. Through this mentoring program and by using community empowerment methods, it is hoped that it can increase knowledge related to SPP-IRT to the wider community, especially home industry activists. The result of this community empowerment is the widespread dissemination of information regarding Home Industry Food Production Certification and the increase in SPP-IRT registrants after this activity takes place. Of course, the success of this activity was accompanied by support from the Ministry of Communication and Information (Kominfo) and Padjadjaran University. The hope is that this program can solve the problem of the lack of MSME participation related to the registration of SPP-IRT for their products.